Changes in Locomotor Activity Observed During Acute Nicotine Withdrawal Can Be Attenuated by Ghrelin and GHRP-6 in Rats - Jázmin Ayman; András Buzás; Roberta Dochnal; Miklós Palotai; Miklós Jászberényi; Zsolt Bagosi (Biomedicines)
Background/Objectives: Ghrelin and growth hormone-releasing peptide 6 (GHRP-6) are peptides which can stimulate GH release, acting through the same receptor. Ghrelin and its receptor have been involved in reward sensation and addiction induced by natural and artificial drugs, including nicotine. The present study aimed to investigate the impacts of ghrelin and GHRP-6 on the horizontal and vertical activity in rats exposed to chronic nicotine treatment followed by acute nicotine withdrawal. Methods: Male and female Wistar rats were exposed daily to intraperitoneal (ip) injection with 2 mg/kg nicotine or saline solution for 7 days, twice a day (at 8:00 and at 20:00). In parallel, the rats were exposed daily to an intracerebroventricular (icv) injection with 1 μg/2 μL ghrelin or 1 μg/2 μL GHRP-6 or saline solution for 7 days, once a day (at 8:00). On the morning of the eighth day (12 h after the last ip administration) and the ninth day (24 h after the last ip administration), the horizontal and vertical activity were monitored in a conducta system. Results: On the eighth day, in nicotine-treated rats a significant hyperactivity was observed, that was reduced significantly by ghrelin and GHRP-6. On the ninth day, in nicotine-treated rats a significant hypoactivity was assessed that was reversed significantly by ghrelin and GHRP-6. Conclusions: Based on the present results, the changes in horizontal and vertical activity observed after 12 and 24 h of nicotine withdrawal can be attenuated by ghrelin and GHRP-6.